Influence of Muscle Mass Area and Visceral Obesity on 30-day Mortality After Colorectal Surgery with Primary Anastomosis - Paulina Moctezuma-Velázquez (Permanyer, 2021)
Background: Muscle mass and visceral fat may be assessed at the level of the third lumbar vertebra (L3) in computed tomography (CT). Both variables have been related with adverse surgical outcomes. Objective: The objective of the study was to study the association of skeletal muscle index (SMI) and visceral fat area (VFA) with 30-day mortality in colorectal surgery. Methods: This is a retrospective cohort study conducted at a tertiary referral hospital in Mexico City. Patients who underwent colorectal surgery with primary anastomosis from January 2007 to December 2018 were included in the study. Their preoperative CT scans were analyzed with the NIH ImageJ software at the level of the third lumbar vertebra to determine their SMI (L3-SMI) and the VFA. Logistic regression analysis (adjusted by surgery anatomical location) was used to determine the association between these variables and surgical 30-day mortality. Results: A total of 548 patients were included; 30-day mortality was 4.18% (23 patients). On univariable analysis, L3-SMI, low SMI, anastomosis leak, pre-operative albumin, estimated blood loss, age, steroid use, Charlson comorbidity index score >2, and type of surgery were associated with 30-day mortality. On multivariable analysis, low SMI remained an independent risk factor with an odds ratio of 4.74, 95% confidence interval 1.22-18.36 (p = 0.02). Conclusion: Low SMI was found to be an independent risk factor for 30-day mortality in patients submitted to colorectal surgery with a primary anastomosis, whether for benign or malignant diagnosis. VFA was not associated with 30-day mortality